Are healthcare providers and young people talking about sexuality? A scoping review to characterize conversations and identify barriers. (29th July 2021) - Lung, Stephanie Lock Man; Wincentak, Joanne; Gan, Caron; Kingsnorth, Shauna; Provvidenza, Christine; McPherson, Amy C.
Abstract: Background: Conversations about sexuality with healthcare providers (HCPs) are critical to youth's positive development, including youth with disabilities or chronic conditions. Yet, little is known about the characteristics of sexuality conversations with youth in healthcare settings. This scoping review examined the nature and extent of sexuality conversations between HCPs and youth (with and without a disability or chronic condition) and aimed to identify barriers to these conversations. Methods: Scoping review methodology using rapid review principles was employed. Inclusion criteria: studies published between 2009 and 2019; examined conversations between HCPs and youth aged 21 and below; addressed sexuality; and took place in a healthcare setting. Study characteristics were described and clustered into thematic groups. Results: Of the 5543 identified, 32 articles were included. Articles addressed (i) the content of sexuality conversations, (ii) prevalence of sexuality conversations and (iii) barriers to discussing sexuality. The content of sexuality discussions was largely biologically focused. The prevalence of sexuality discussions varied, with some discrepancy between youth‐reported and HCP‐reported rates. Seven barriers (three personal and four systemic) were identified. Youth with disabilities or chronic conditions were vastly under‐represented in the published literature. Conclusions: This study highlighted that sexuality is an underexplored topic between HCPs and young people, especially young people with disabilities and/or chronic conditions. Given the importance of sexuality to young people's mental and physical health, research addressing barriers to these discussions and development of evidence‐informed resources to support HCPs and youth to engage in conversations about sexuality should be a priority.